ANALISIS HUKUM PELAKSANAAN ALIH FUNGSI TANAH PERTANIAN MENJADI TANAH PERUMAHAN DI KABUPATEN SERDANG BEDAGAI - PARLINDUNGAN SIANIPAR (PREMISE LAW JURNAL, 2016)
Serdang Bedagai Regency is one of the areas in North Sumatera Province which has the area of 1,900.22 km2, consisting of 17 subdistricts and 243 villages with the population of 602,522. It is one of village rice barns in North Sumatera Province, and its rice production is increasing each year and has the potency for developing agribusiness, but in 2015 it decreased because agricultural land area became less and less. In 2010 it was 41,057 hectares, but in the period of 2011-2015 it decreased drastically to 38,502 hectares which decreased 2,555 hectares or 16% within 5 years; this was because it was shifted its function to residential or industrial land. The research problems were whether there was the acceleration of agricultural land transfer to residential land, how about the impact of agricultural land transfer to residential land, and how about the role of Government in coping with the acceleration of agricultural land transfer to residential land in Serdang Bedagai Regency. Keywords: Land Transfer, Agricultural Land, Residential Land